OBSTETRIC PREDICTORS OF PURULENT-SEPTIC DISEASES AFTER CAESAREAN SECTION - Заграт Шехмагомедовна Мажидова; Ильнур Ирекович Мусин; Альфия Галимовна Ящук; Эдвард Александрович Берг; Лилиана Анасовна Даутова (The Publishing House Medicine and Enlightenment, 2023)
Purpose of the study - to study the role of significant risk factors and metabolic disorders in full-term pregnant women in the development of purulent-septic complications after caesarean section in the lower uterine segment. Materials and methods. The authors of this article analyzed obstetric complications after caesarean section in the lower uterine segment. Retrospectively, 862 women were divided into 2 groups depending on the presence of purulent-septic complications. The group of purulent-septic complications included 81 puerperas, and the group without complications included 781 patients. For statistical processing of the obtained results, the STATISTICA 10.0 and Eviews 12.0 software packages were used. Results. Performing an emergency cesarean section in childbirth, namely in the presence of anomalies of labor activity that are not amenable to medical correction (OR = 2.49, CI 95% 1.2-5.0), and after 12 hours after the discharge of amniotic fluid (OR = 4.66, 95% CI 2.3-9.4) increase the risk of purulent-septic complications in the postpartum period. Conclusion. An analysis of obstetric factors in the development of purulent-septic complications revealed an association with the presence of pathological total weight gain during pregnancy, an increase in the duration of the anhydrous period of more than 12 hours, and emergency abdominal delivery, more often during childbirth. Pathological overall weight gain during pregnancy, indicating impaired metabolism of substances during gestation, an increased risk of diabetes mellitus, increases the risks of purulent-septic complications (OR = 3.6, 95% CI 1.9-6.7).